2021
DOI: 10.1177/03128962211032448
|View full text |Cite
|
Sign up to set email alerts
|

Fintech and responsibility: Buy-now-pay-later arrangements

Abstract: Buy-now-pay-later (BNPL) arrangements have rapidly emerged as a short-term debt option, and like other innovative and disruptive Fintech, challenge existing regulation. BNPL arrangements avoided prescribed ‘responsible lending’ legislative obligations, which applied to similar short-term credit products. Instead, BNPL relies on ‘responsible spending’ in providing a potentially cheaper option than alternatives such as credit cards. We describe the interplay of regulation and responsibility with BNPL. A survey i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 20 publications
0
23
0
2
Order By: Relevance
“…An analysis of the over‐indebtedness of UK consumers showed that consumers from low‐income households with low levels of financial literacy and poor credit histories are vulnerable to lenders who offer easily accessible consumer credit facilities (Disney et al, 2008). Perception of the benefits and risks of BNPL have been found to be related to financial literacy in a study among Australian university students (Gerrans et al, 2021). Those with a higher level of financial literacy believe that BNPL is riskier and less beneficial than people with a lower level of financial literacy.…”
Section: Literature Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of the over‐indebtedness of UK consumers showed that consumers from low‐income households with low levels of financial literacy and poor credit histories are vulnerable to lenders who offer easily accessible consumer credit facilities (Disney et al, 2008). Perception of the benefits and risks of BNPL have been found to be related to financial literacy in a study among Australian university students (Gerrans et al, 2021). Those with a higher level of financial literacy believe that BNPL is riskier and less beneficial than people with a lower level of financial literacy.…”
Section: Literature Surveymentioning
confidence: 99%
“…In relation to financial products, it is generally recognised that regulation has an important role to play and that early regulatory intervention in the product cycle is likely to have a much better consumer impact (O'Brien, 2012). Gerrans et al (2021) find that, as BNPL is unregulated, it places greater responsibility on the financial behaviours of the purchaser, which is problematic given that the primary users are younger adults who are a vulnerable group with relatively low financial literacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Enhance topic was research that investigates how traditional financial products and services are implemented and improved by using fintech. Examples include using fintech to improve the traditional activities of making personal consumer loans (Di Maggio & Yao, 2021 ; Gerrans et al, 2021 ), analyzing the creditworthiness of borrowers (Jagtiani & Lemieux, 2019 ), and enhancing customer experience in traditional wealth management (Kim et al, 2020 ). The Impact topic analyses fintech’s influence on industries, governments, and economies and includes the impact of technology on banking industry misconduct (Bertsch et al, 2020 ), fragility of financial institutions that use various technologies (Fung et al, 2020 ), how various technologies are affecting the insurance industry (Stoeckli et al, 2018 ), and the new regulatory models necessary from fintech (Jiang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Według jednej z definicji BNPL, to innowacyjne rozwiązania FinTech, opierające się na "odpowiedzialnym wydawaniu" i stanowiące tańszą alternatywę dla kart kredytowych (Gerrans i in., 2022). Natomiast FinTech, zgodnie z definicją zaproponowaną przez K. Świeszczaka, to sektor, do którego należą przedsiębiorstwa wykorzystujące innowacyjne rozwiązania technologiczne w procesach związanych ze świadczeniem usług finansowych (Świeszczak, 2019, s. 147).…”
Section: Zagadnienia Definicyjneunclassified